Immunosuppression considerations in simultaneous organ transplant. Issue 1 (24th January 2021) - Kovac, Danielle; Choe, Jason; Liu, Esther; Scheffert, Jenna; Hedvat, Jessica; Anamisis, Anastasia; Salerno, David; Lange, Nicholas; Jennings, Douglas L.
Abstract: Solid organ transplantation is a life‐saving procedure for patients in the end stage of heart, lung, kidney, and liver failure. For patients with more than one failing organ, simultaneous organ transplantation has emerged as a viable treatment option. Immunosuppression strategies and outcomes for simultaneous organ transplant recipients have been reported, but often involve limited populations. Transplanting dual organs poses challenges in terms of balancing immunosuppression with immunologic risk and allograft damage from surgical complications. Furthermore, transplanting certain organs can impose considerations on the management of immunosuppression. For example, liver allografts may confer immunologic privilege and lower rates of rejection of other allografts. This review article evaluates immunosuppression strategies for simultaneous kidney‐pancreas, liver‐kidney, heart‐kidney, heart‐liver, heart‐lung, lung‐liver, and lung‐kidney transplants. To date, no comprehensive review exists to address immunosuppressive strategies in simultaneous organ transplant populations. Our review summarizes the available literature and provides evidence‐based recommendations regarding immunosuppression strategies in simultaneous organ transplant recipients.